O feito diferencial galego como máximo expoñente da literatura rexional. A Biblioteca de Escritores Gallegos - Carlos , Gegúndez López (Madrygal. Revista de Estudios Gallegos, 2010)
This article reviews the cultural work developed by the Galician Writers Library on the centenary of its fundation. The founders of this collection were looking for the promotion and diffusion of the so called Galician regional literature from Madrid.